2015
DOI: 10.1016/j.exger.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Attention enhancing effects of methylphenidate are age-dependent

Abstract: The psychostimulant methylphenidate (MPH, Ritalin®) is used to treat a variety of cognitive disorders. MPH is also popular among healthy individuals, including the elderly, for its ability to focus attention and improve concentration, but these effects have not been shown to be comparable between aged and adult subjects. Thus, we tested whether MPH would improve performance in sustained attention in both adult and aged rats. In addition, we tested the impact of visual distraction on performance in this task an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…In contrast to the therapeutic effects of low-dose MP in the ELS ADHD-type animals, MP treatment in control animals in general induced hyperactive behavior and reduced attentiveness. Pharmacological studies, which tested the behavioral effects of MP treatment in behaviorally normal rodents, also observed typical stimulant effects such as increased locomotor activity (Thanos et al 2015 ; Haleem et al 2015 ; Berridge et al 2006 ), but in contrast to our study improved attention (Bhattacharya et al 2015 ).…”
Section: Discussioncontrasting
confidence: 41%
“…In contrast to the therapeutic effects of low-dose MP in the ELS ADHD-type animals, MP treatment in control animals in general induced hyperactive behavior and reduced attentiveness. Pharmacological studies, which tested the behavioral effects of MP treatment in behaviorally normal rodents, also observed typical stimulant effects such as increased locomotor activity (Thanos et al 2015 ; Haleem et al 2015 ; Berridge et al 2006 ), but in contrast to our study improved attention (Bhattacharya et al 2015 ).…”
Section: Discussioncontrasting
confidence: 41%
“…Patients included in this multinational study were mainly adults (94.7%), of which, 47.3% were aged ≥65 years. Hence, we believe this age group is likely to have received methylphenidate for mixed purposes 36 such as ADHD, cognitive impairment, 37 revitalizations, 38,39 or palliative care 40 . Our age‐stratified analysis of patients aged ≥20 years also showed that methylphenidate did not trigger myocardial infarction as its incidence rate was already increased in the period prior to initiating methylphenidate.…”
Section: Discussionmentioning
confidence: 61%
“…Normal age-related cognitive decline is related to pharmacological therapies (Hanlon et al, 2001); but until recently, evidence concerning the safety of these treatments was lacking (Bhattacharya et al, 2015). Physical activity (PA) might offer hope for combating the deleterious effects of dementia while simultaneously reducing the need for pharmacological interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, these losses may proceed to more serious cognitive disorders, such us dementia and functional mobility impairment (Bhattacharya et al, 2015). Executive functioning and attention are important in the regulation of functional mobility (MonteroOdasso et al, 2009).…”
Section: Introductionmentioning
confidence: 99%